2022
DOI: 10.1001/jamanetworkopen.2022.35068
|View full text |Cite
|
Sign up to set email alerts
|

Association of Plasma and Cerebrospinal Fluid Alzheimer Disease Biomarkers With Race and the Role of Genetic Ancestry, Vascular Comorbidities, and Neighborhood Factors

Abstract: ImportanceDifferences in cerebrospinal fluid (CSF) tau Alzheimer dementia (AD) biomarkers by self-identified race have been observed in prior studies. More recently, plasma biomarkers have been gaining recognition, but whether they exhibit similar differences is unclear. Furthermore, the underlying explanation for these differences in AD biomarkers is still unexplored.ObjectivesTo investigate differences in plasma biomarkers by race and genetic ancestry and explore potential underlying explanations for these d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 51 publications
(79 reference statements)
1
20
0
Order By: Relevance
“…9 This study of a large, biracial, community-based sample of adults provides evidence that sex differences and systemic medical comorbidities, but not self-reported race/ethnicity, influence variation in plasma AD biomarkers and therefore need to be accounted for in the development of reference ranges and guidance on clinical interpretation. 10 That study sample consisted predominantly of individuals with MCI and those in a younger age range than ours. In addition, that study did not match on age (AA participants were younger than NHW participants) and did not consider CKD, which is known to elevate plasma biomarker levels.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…9 This study of a large, biracial, community-based sample of adults provides evidence that sex differences and systemic medical comorbidities, but not self-reported race/ethnicity, influence variation in plasma AD biomarkers and therefore need to be accounted for in the development of reference ranges and guidance on clinical interpretation. 10 That study sample consisted predominantly of individuals with MCI and those in a younger age range than ours. In addition, that study did not match on age (AA participants were younger than NHW participants) and did not consider CKD, which is known to elevate plasma biomarker levels.…”
Section: Discussionmentioning
confidence: 82%
“…A prior study of adults from the greater Atlanta metropolitan area reported lower levels of plasma Aβ 40 , Aβ 42 , p-tau 181 , and NfL in AA individuals compared with those in NHW individuals. 10 That study sample consisted predominantly of individuals with MCI and those in a younger age range than ours. In addition, that study did not match on age (AA participants were younger than NHW participants) and did not consider CKD, which is known to elevate plasma biomarker levels.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Minoritized groups have a higher risk of AD dementia [18][19][20], making it especially problematic that they are underrepresented in AD research [21]. Several studies have found racial differences in AD biomarkers, including lower average CSF total tau and p-tau181 concentrations in Black or African American compared to non-Hispanic White participants [22][23][24][25]. Although AD blood tests may perform differently across racial groups in predicting AD pathology [25], this is difficult to clearly establish because so few individuals from minoritized groups have samples available for analysis [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Minoritized groups have a higher risk of AD dementia, 18–20 making it especially problematic that they are underrepresented in AD research 21 . Several studies have found racial differences in AD biomarkers, including lower average CSF total tau and p‐tau181 concentrations in Black or African American compared to non‐Hispanic White participants 22–25 . Although AD blood tests may perform differently across racial groups in predicting AD pathology, 25 this is difficult to clearly establish because so few individuals from minoritized groups have samples available for analysis 26,27 .…”
Section: Introductionmentioning
confidence: 99%